Methodology for the development of the sensory-perceptual capacity of badminton players during the tactical preparation process (Original) (Revista científica Olimpia, 2020)
Based on the particularities of the sport of Badminton and the athletes who practice it, the work of the sensorial-perceptual capacity is promoted during tactical preparation as one of the fundamental points for achieving good results. The objective of the research is to elaborate a methodology for the development of sensorial perceptual capacity during the tactical preparation of badminton players category 11-12 years, based on a theoretical conception with a personalized, dynamic and developer approach.It provides badminton coaches with a methodology that groups together the essential elements for the development of sensory-perceptual capacity during the tactical preparation of badminton players in the sports training process in Santiago de Cuba province. Content in exercises of spatial perception, complex reaction speed and hitting decision. It works in all stages of the training process and this research is framed to the work of the individual modality for both sexes category 11-12 years. The research process has required empirical, theoretical and statistical-mathematical methods.Through the case study method, the effectiveness of the application of the methodology demonstrated in satisfactory results to four badminton players was corroborated. Susceptible to generalize the proposal.
Keywords: badminton athletes, badminton players' tactical preparation, development of sensory-perceptual capacity